Rehabilitation of Wastelands through Fruit Orchard Plantations - Negi, R. S.; Pathak, Bharat; Sikarwar, R. L. S. (Indian Forester, 2014)
In India approximately 68.35 million hectare area of the land is lying as wastelands. Out of this lands, approximately 50% lands are such, which can be put to socially productive uses if treated properly. Much of these lands are suitable for fruits plantation and could be used to help increase supplies of fruits, not available in sufficient quantities to meet the current demand. Fruit orchard-based land-management strategies can contribute significantly to productive uses of waste lands and minimize the level of malnutrition. Suitable technologies (fruit species, micro site improvement, planting method, in-situ moisture conservation, and propagation) have been developed which can be used with great success for planting of fruit crops on wastelands. An attempt has been made to review the information available on the matter of rehabilitation of wastelands through fruit plantations with a view to have its utility in undertaking the work on task basis.